Anais Do XIV Encontro Nacional De Estudantes De Engenharia Ambiental 2016
DOI: 10.5151/engpro-eneeamb2016-rh-004-4914
|View full text |Cite
|
Sign up to set email alerts
|

Aquaponia Como Alternativa Para O Cultivo De Peixes E Hortaliças

Abstract: Resumo: A aquaponia é um método que une dois tipos de produção em um só local: produção de peixes em cativeiro e hidroponia (cultivo de hortaliças em meio aquoso). O presente projeto foi realizado no Campo-Escola de Tecnologia Social (CELOGS), situado no Campus I da Universidade Católica de Brasília. Partindo-se do interesse de demonstrar que a aquaponia é uma alternativa para o cultivo de hortaliças e também uma forma de tratamento da água, o presente trabalho teve como objetivo geral dimensionar um projeto d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Through the data obtained (Figure 6), it is possible to determine that, in the experimental system, bacteria and fish were subjected to excellent conditions, but the ideal range for plants was not reached. Thevalues were similar to results obtained by Kuhnen et al (2016), who found pH in the range of 7.5 to 7.9.…”
Section: Phsupporting
confidence: 91%
“…Through the data obtained (Figure 6), it is possible to determine that, in the experimental system, bacteria and fish were subjected to excellent conditions, but the ideal range for plants was not reached. Thevalues were similar to results obtained by Kuhnen et al (2016), who found pH in the range of 7.5 to 7.9.…”
Section: Phsupporting
confidence: 91%
“…17 Many studies are developed to prove the economic viability of aquatic vegetable and aquatic organism production. 2,6,[18][19][20][21] Was investigated the viability of aquaponic production in the state of Hawaii through a case study carried out on three producing farms, the study found that even small scale production farms obtained profitable rates, indicating that aquaponics can be a viable option for the production of vegetables and fish for local markets. 22 Another study was analyzed an integrated tilapia and lettuce production system, considered a practical and profitable enterprise.…”
mentioning
confidence: 99%
“…26,27 To implement sustainable food production systems that use more efficient technologies (such as aquaponics), it is essential to consider the structural factors in a broad way, in addition to the technical and physiological needs at the heart of food production and behavior consumption among consumers. 4 Several authors highlight the importance of consumer feeling for the development of an aquaponic industry 18,[28][29][30] and for sustainable agriculture in general. 31 The aquaponic system is still relatively new.…”
mentioning
confidence: 99%